Étude croisée du rapport aux savoirs à l'égard des sciences naturelles et des sciences humaines et sociales : portraits d'élèves de la fin du secondaire au Québec - Geneviève Therriault; Agnieszka Jeziorski; Barbara Bader; Émilie Morin (Nantes Université, 2018)
This article offers a cross study of the relationship to knowledge regarding the natural sciences and the humanities and social sciences, from the point of view of secondary school students in Quebec. It is an extension of studies in science education and humanities which tends to strengthen civic engagement and the teaching and learning of socio-controversial issues at the secondary level, in order to enhance various facets of the relationship to knowledge and to the act of learning of young people. Several studies have analyzed the relationship to knowledge of students about natural sciences. However, very little research has attempted to characterize the relationship to knowledge toward humanities and social sciences then to draw distinctions with respect to relationship to knowledge in the natural sciences. This study aims to analyze the relationship to knowledge about each of the two areas and then identify possible links between them. To do this, we appeal to a conceptualization incorporating the viewpoints of two contrasting disciplinary fields, within epistemic, identity and social dimensions of the concept of relationship to knowledge. In terms of method, two data collection instruments are mobilized: a questionnaire name "bilan de savoirs" and the semi-structured interview. The sample includes 41 secondary V students of Quebec state, who responded to the questionnaire. After, 10 students participated to the interviews in order to deepen the answers given previously and address new aspects. The results allow to draw parallels but also distinctions between the relationship to knowledge in respect of the natural sciences and humanities and social sciences. Finally, the results lead us to formulate proposals for teacher education in which the practice of interdisciplinarity in secondary schools is encouraged.